2014
DOI: 10.1002/macp.201400140
|View full text |Cite
|
Sign up to set email alerts
|

2‐(1‐(2,4‐Bis((di(4‐fluorophenyl)methyl)‐6‐methylphenylimino)ethyl)‐6‐(1‐(arylimino)ethyl)pyridylmetal (iron or cobalt) Complexes: Synthesis, Characterization, and Ethylene Polymerization Behavior

Abstract: A series of 2‐(1‐(2,4‐bis((di(4‐fluorophenyl)methyl)‐6‐methylphenylimino)ethyl)‐6‐(1‐(aryl­imino)ethyl)pyridines is synthesized and used to form their corresponding iron(II) and cobalt(II) chloride complexes thereof. All the organic compounds are fully characterized by elemental analysis, and IR and 1H/13C NMR spectroscopy, whereas the corresponding iron and cobalt complexes are characterized by elemental analysis and IR spectroscopy, as well as single‐crystal crystallography for the Fe2, Co1, and Co2 complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 38 publications
6
64
0
Order By: Relevance
“…Over the last five years, our group has also been interested in improving the catalytic activity and thermal stability of bis(arylimino)pyridine-iron and -cobalt complexes [43,46,51]. In particular we have found that the introduction of sterically demanding benzhydryl groups and their derivatives into the N,N,N-ligand frame of their iron and cobalt catalysts can be influential (14-30, Figure 14) [70][71][72][73][74][75][76][77][78][79][80][81] for ethylene polymerization (see Table 2).…”
Section: < Figure 13>mentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last five years, our group has also been interested in improving the catalytic activity and thermal stability of bis(arylimino)pyridine-iron and -cobalt complexes [43,46,51]. In particular we have found that the introduction of sterically demanding benzhydryl groups and their derivatives into the N,N,N-ligand frame of their iron and cobalt catalysts can be influential (14-30, Figure 14) [70][71][72][73][74][75][76][77][78][79][80][81] for ethylene polymerization (see Table 2).…”
Section: < Figure 13>mentioning
confidence: 99%
“…Benzhydryl-substituted bis(arylimino)pyridine-iron and -cobalt complexes 14-31 [70][71][72][73][74][75][76][77][78][79][80][81]…”
Section: Figure 14mentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Moreover, late-transition-metal complexes are promising for industrial processes producing novel advanced polyolefi n materials, [5] while computation simulation is promising for the design and prediction of effective catalysts, along with the production of advanced polyolefi ns. [6] Furthermore, new techniques have been developed for the measurement of microstructures of polyoelfi ns.…”
Section: The 60th Birthday Of Prof Minoru Teranomentioning
confidence: 99%
“…To this end, we screened various modified bis(imino)pyridine derivatives. High thermal stability of corresponding bis(imino)pyridyl iron complexes was achieved by using bis(imino)pyridines with dibenzhydryl‐ and bis(4‐fluorophenyl)methyl‐substituents . The above catalysts displayed high apparent activities (recalculated from PE yields within 15 or 30 min) at temperatures up to 80°C upon the activation with MAO and MMAO, and the sophisticated ligand architectures provided rich opportunities for controlling the temperature stability, as well as molecular weights and polydispersities …”
Section: Introductionmentioning
confidence: 99%